The Histopathological Features of Syphilis and Its Mimickers - Purnamasari, Indah; Hidayati, Afif Nurul; Kusumastuti, Etty Hary; Effendy, Isaak (Folia Medica Indonesiana, 2023)
Highlights: • The importance of having a strong suspicion for syphilis and maintaining close contact between dermatologists and pathologists cannot be understated. • Understanding the clinical relationship and histopathological features of syphilis is crucial for accurate diagnosis and distinction from its histopathologic mimickers. Abstract: Settings Syphilis, also known as "the great imitator," is a sexually transmitted infection with a variety of clinical symptoms and histopathological similarities to other infectious diseases. Public health concerns about syphilis have grown significantly. Since 2000, there has been an increase in syphilis prevalence in the United States, with a 17.6% increase from 2015 to 2016. From 2000 to 2019, the number of syphilis cases throughout Asia increased from 0.9% to 30.9%, whilst the number of cases in Indonesia decreased from 22.5% to 14.4%. Specific serological tests for syphilis can usually detect and confirm the diagnosis and offer follow-up care in most cases. However, in certain instances, the clinical characteristics discovered during testing can be identical to those of other diseases, which may lead to inconsistent diagnosis. Considering that the diagnostic pathology is pertinent to the clinical circumstances, a histopathological investigation may be useful for differentiating syphilis mimickers. Pathology is essential for identifying potential syphilis patients with ambiguous clinical symptoms. This study's purpose was to assist dermatologists and pathologists in identifying "mimickers" that require a biopsy and in determining the correct diagnosis and treatment coutsed based on etiology.